Nucleophile-mediated oxa-Michael addition reactions of divinyl sulfone – a thiol-free option for step-growth polymerisations. Issue 12 (12th October 2015) - Strasser, Simone; Slugovc, Christian
Abstract : The first example of an aa–bb-type nucleophile-mediated oxa-Michael addition polymerisation reaction is reported. Abstract : Triphenylphosphine and 4-dimethylaminopyridine promote the oxa-Michael addition reaction of alcohols and divinyl sulfone. Under solvent-free conditions, the reaction is particularly fast and allows for the preparation of polymers.